Cartographie De La Vulnérabilité À La Pollution Des Aquifères Du Socle Précambrien : Cas De La Région D’oumé (Centre-Ouest De La Côte D’ivoire) - Blanchard, Allechy Fabrice; Théophile, Lasm; Marc, Youan Ta; François, Yao Kouadio Assemien; Suzane, Kouakou Ourapa; Raphaël, Oka Koua Armel; Derving, Baka; Zephir, De Lasme Omer (European Scientific Journal, ESJ, 2016)
Development of agricultural and mining activities and the rapid growth of the population (3.8%) in Oumé’s area, constitute a potential risk of groundwater’s pollutions. This study interested Oumé’s area and aims to elaborate a map of vulnerability to pollution for a better management of groundwaters. The database is constituted by various data in particular, geological, hydrogeological, geomorphological, pluviometric data and satellite image. Methods DRASTIC and GOD were used in this study. Results of DRASTIC method indicated that 31.86% of study area have a very low vulnerability, 68.12% a low vulnerability and 0.02% a moderate vulnerability. With GOD method, 12.8% of study area have a very low vulnerability, 86.46% a low vulnerability and 0.74% a moderate vulnerability. The chemical analysis of groundwater showed that weaker rates of nitrates (0-14mg/l) registered inside the surely well protected zones. These observations have led to validate some various maps obtained. Result of the test of Kappa revealed that coefficient K is reliable and gave moderate agreement (K=0.43) between both methods. This agreement is confirmed by the surface analysis (79.01%). In this study, the DRASTIC method supplied better results and is thus better adapted for the evaluation of vulnerability in the pollution of groundwater of this area.